Perbedaan Tingkat Kecemasan Mahasiswa Keperawatan Universitas Advent Indonesia yang Sedang Menjalani Sistem Blok dan Sistem SKS (Journal of Telenursing (JOTING), 2025)
This study aims to identify differences in anxiety levels of nursing students undergoing block systems and SKS systems at Universitas Advent Indonesia. The method used is comparative quantitative research with a cross-sectional approach. The results showed that 50% of SKS system students experienced low anxiety, 30% moderate, and 20% high. In block system students, 54% were at low anxiety, 31% moderate, and 14.9% high. The average anxiety score of SKS system students was 22.95, while the block system was 20.84. The significance value of the Mann-Whitney test was p-value = 0.455 (> 0.05), which indicated that there was no significant difference in anxiety levels between the two groups. In conclusion, although the average anxiety in SKS system students was slightly higher, statistically there was no significant difference between the two groups. Keywords: Students, Block System, SKS System, Anxiety Level